Copper-containing titanium alloy bionic surface based on Mg and Cu ion sequential release and preparation method

By using copper-containing titanium alloy bionic surface based on Mg and Cu ion timing released in surgical implant treatment for diabetic patients, the implant failure and delayed bone healing caused by dysfunction of bone immune response in diabetic patients was solved, and bone healing was achieved and significantly improve the antibacterial effect.

CN119464787APending Publication Date: 2025-02-18INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411436269.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18

Smart Images

  • Figure CN119464787A_ABST
    Figure CN119464787A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of surgical implantation treatment instruments for diabetic patients, and particularly discloses a copper-containing titanium alloy bionic surface based on Mg and Cu ion sequential release and a preparation method. The method comprises the steps that a copper-containing titanium alloy cast ingot is prepared through smelting of a vacuum consumable electric arc furnace, then forging, heat treatment and cooling are conducted on a copper-containing titanium alloy cast ingot blank, and the copper-containing titanium alloy bionic surface is obtained. An experimental sample is obtained through linear cutting, the surface of the sample is polished with abrasive paper, then the experimental sample is placed in a crucible, Mg particles are poured into the crucible till the surface of the sample is completely covered with the Mg particles, dealloying treatment is conducted in a muffle furnace in the argon environment, and the bionic surface is obtained. The surface is a porous composite bionic surface with magnesium-rich pores, the ligament width is 0.5-10.5 mu m, and the ligament thickness is 3-20 mu m. According to the bionic surface, the macrophages can be gradually converted from the M1 pro-inflammatory phenotype to the M2 pro-repair phenotype, and the optimal osteogenesis promoting and anti-inflammatory functions are achieved. The method is expected to solve the problem of clinical pain points of high-incidence titanium-based implant bone healing failure of diabetic patients, and has extremely high clinical application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surgical implant treatment devices for diabetic patients, and in particular to a copper-containing titanium alloy bionic surface based on the timed release of Mg and Cu ions and a preparation method thereof. Background Art

[0002] Diabetes has become one of the systemic diseases that threaten human health and life. The bone repair and regeneration process of diabetic patients is significantly impaired. Osteoporosis and fractures are common complications of diabetic patients, involving multiple organs such as joints, oral cavity, and feet. Implanting artificial prostheses (mostly titanium alloys) to restore the normal function of defective bone tissue is the preferred option for treating fractures. However, for this special group of diabetic patients, the high sugar environment increases the risk of implant failure by 2.75 times compared with ordinary patients, and delays fracture healing by 1.6 times.

[0003] The success of implant treatment depends on the healing of the surrounding bone tissue, and the immune response is the key link to ensure that the bone healing process changes from the early inflammatory stage to the healing and repair stage. Macrophages (MΦ) are one of the most important effector cells in the immune response. The conversion of macrophages from M1 phenotype to M2 phenotype regulates the process of bone healing from pro-inflammatory to regenerative. However, the diabetic environment destroys the plasticity of macrophage metabolism and function, causing macrophages to remain in the M1 phenotype and unable to transform into the M2 phenotype, causing bone immune response disorders and delaying the bone healing process around the implant. In addition, bone immune response disorders also weaken the ability of the immune system to clear bacteria, increasing the risk of bacterial infection around implants in diabetic patients. It can be seen that bone immune response disorders are the main reason for aggravating implant failure in diabetic patients.

[0004] In view of the problem of implant failure due to bone immune disorders in surgical implant treatment of diabetic patients, the clinical treatment method mainly uses hypoglycemic drugs to control blood sugar index at 6.1~9.0 mmol / L before, during and during the healing process, and uses antibiotics to promote wound healing. However, a 5-year clinical follow-up study found that the implant failure rate of diabetic patients was still as high as 10.2%, which was significantly higher than the implant failure rate of normal patients (1~4.7%). It can be seen that the treatment method of simply controlling blood sugar concentration still cannot fully guarantee the long-term use of implants in diabetic patients. Summary of the invention

[0005] The titanium-based implants currently used in clinical practice are a type of biologically inert material that lacks the function of correcting bone immune disorders in diabetic patients. In order to endow titanium-based implants with bone immune regulation, reshape the phenotype and function of macrophages in a diabetic environment, and thereby promote bone healing around implants and inhibit the occurrence of bacterial infection, the purpose of the present invention is to provide a copper-containing titanium alloy bionic surface based on the timed release of Mg and Cu ions and a preparation method thereof.

[0006] The invention provides a copper-titanium alloy bionic surface based on the timed release of Mg and Cu ions. The surface is a porous composite bionic surface with magnesium-rich pores, a ligament width of 0.5-10.5 μm, and a thickness of 3-20 μm.

[0007] The alloy bionic surface of the present invention can realize the in-situ timed release of Mg and Cu elements, improve the mitochondrial function of macrophages, and realize the bone immune regulation. At the same time, the high porosity, ideal pore size and low elastic modulus of the alloy bionic surface can promote cell adhesion and differentiation, which is beneficial to improve the biological fixation effect of implants in the diabetic environment.

[0008] The invention provides a preparation method of a copper-containing titanium alloy bionic surface based on the timed release of Mg and Cu ions. The preparation method comprises the following steps: preparing a copper-containing titanium alloy ingot by smelting in a vacuum consumable arc furnace, forging the titanium alloy ingot blank, heat treating and cooling it, obtaining an experimental sample by wire cutting, polishing the sample surface with sandpaper, placing the experimental sample in a crucible, pouring Mg particles into the crucible until the sample surface is completely covered by the Mg particles, and performing dealloying treatment in a muffle furnace under an argon environment to obtain a bionic surface.

[0009] The present invention provides a method for preparing a copper-containing titanium alloy bionic surface based on the sequential release of Mg and Cu ions, wherein the copper-containing titanium alloy has a Cu content of 0-10 wt.% (preferably 5 wt.%). The forging temperature is 900-1200°C (preferably 900°C). The heat treatment temperature is 700-900°C (preferably 850°C), and the heat treatment time is 0-2 h (preferably 2 h). The experimental sample obtained by wire cutting is a disc with a diameter of 10 mm and a thickness of 2 mm. The sandpaper is at least one of 60#, 120#, 180#, 240#, and 1000# (preferably 180#), and the surface roughness of the alloy is adjusted. The Mg particles are high-purity magnesium particles, preferably with a purity of 99.99% and a particle size of 20 meshes. The dealloying treatment temperature is 700-900°C (preferably 900°C), and the holding time is 0-3h (preferably 3 h).

[0010] Advantages of the present invention: The Ti-Cu alloy bionic surface structure that can achieve the timed release of Mg and Cu ions prepared by the method of the present invention is closer to the three-dimensional structure of human bones, which not only promotes the regeneration of new bone tissue, but also can reduce the elastic modulus of the implant surface, reduce the influence of stress shielding, and is more suitable for diabetic patients with damaged bones. In addition, the timed release of Mg and Cu ions can reshape the phenotype and mitochondrial function of macrophages in the diabetic environment and accelerate the repair of bone tissue. At the same time, the continuous release of Mg ions will regulate the expression of specific inflammatory factors and significantly inhibit the mineralization and maturation of bone tissue. Cu ions play a role in regulating metabolic pathways, promoting microorganisms to metabolize sugars through the tricarboxylic acid cycle and oxidative phosphorylation, inhibiting the glycolysis pathway, and then inhibiting the occurrence of peri-implant infection and accelerating bone healing around the implant. This Ti-Cu alloy bionic surface structure with timed release of Mg and Cu ions has extremely high clinical application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The expression of M1 and M2 phenotype marker genes in RAW264.7 cells; Figure 2 The gene expressions of ALP (a), OPN (b), COLI (c), and Runx2 (d) in MC3T3-E1 cells under the diabetic microenvironment remodeled by different alloy bionic surfaces; Figure 3 To simulate the bionic surfaces of different alloys in the diabetic environment, (a) typical photos of Staphylococcus aureus strains; (b) antibacterial rate; (c) SEM photos; Figure 4 RNA-seq transcriptomic analysis to study bone immune regulation in a simulated diabetic environment: gene expression; Figure 5 RNA-seq transcriptomic analysis to study the role of bone immunity regulation in a simulated diabetic environment: analysis of differentially expressed genes; Figure 6 RNA-seq transcriptomic analysis to study the role of bone immunity regulation in a simulated diabetic environment: GO functional downregulated gene analysis; Figure 7 RNA-seq transcriptomic analysis to study the role of bone immunity regulation in a simulated diabetic environment: GO functional upregulated gene analysis; Figure 8 RNA-seq transcriptomic analysis to study the role of bone immunity regulation in a simulated diabetic environment: KEGG metabolic down-regulation pathway analysis; Fig. 9 RNA-seq transcriptomic analysis to study osteoimmunomodulatory effects in a simulated diabetic environment: KEGG metabolic upregulated pathway analysis. DETAILED DESCRIPTION

[0012] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0013] Example: Example 1-12 is a copper-containing titanium alloy bionic surface that regulates macrophage phenotype and mitochondrial function by sequential release of Mg and Cu ions. The chemical composition of the copper-containing titanium alloy and the liquid magnesium dealloying treatment process of the alloy surface are shown in Table 1, specifically: ① Examples 1-4 are bionic surfaces obtained by polishing the Ti-5Cu alloy surface with 180# sandpaper and then subjecting the surface to liquid magnesium dealloying treatment at 900°C for 0.25, 0.5, 1, and 3 h, respectively. Among them, the bionic surface dealloyed for 3 h has the optimal "ligament width-thickness" match.

[0014] ②Examples 4-6 are bionic surfaces obtained after the Ti-5Cu alloy surface was polished with 180# sandpaper and then dealloyed with liquid magnesium at 900, 800, and 700°C for 3 hours, respectively. The bionic surface obtained at a dealloying temperature of 900°C has the optimal "ligament width-thickness" match.

[0015] ③ Examples 4, 7-10 are bionic surfaces obtained after the Ti-5Cu alloy surface was polished with 180#, 60#, 120#, 240#, and 1000# sandpapers, respectively, and then dealloyed with liquid magnesium at 900°C for 3 h. Among them, the bionic surface obtained after polishing with 180# sandpaper before dealloying treatment has the optimal "ligament width-thickness" match.

[0016] ④ Examples 4, 11, and 12 are bionic surfaces obtained by polishing the Ti-xCu (x=5, 7, 10) alloy surface with 180# sandpaper and then subjecting the surface to liquid magnesium dealloying treatment at 900°C for 3 h. The bionic surface obtained with the Ti-5Cu alloy has the optimal “ligament width-thickness” match.

[0017] Comparative Examples 1-4 are copper-containing titanium alloy and pure titanium surfaces with the same roughness as that of clinical dental implants after sandblasting and acid etching (Sa: 1-2 μm).

[0018] Table 1 Surface treatment process of materials in examples and comparative examples In order to illustrate the technical concept and features of the present invention, only Example 4 and Comparative Examples 1 and 4 with the best "ligament width-thickness" matching are selected as representatives to illustrate the performance detection method of the embodiment: 1. Name and labeling of performance test samples: LMD-A has the function of sequential release of Mg and Cu ions. (HNO3 acid etching time in Example 4 is 1 min)

[0019] LMD-A-5h: The effect of the three-dimensional structure and the effect after implantation. (HNO3 acid etching time of Example 4 is 5 h)

[0020] TiCu group: reflects the effect of copper addition. (Comparative Example 1)

[0021] Ti group control: reflects the immune and bone healing status of current clinical implants in a diabetic environment. (Comparative Example 4)

[0022] 2. Detection of polarization state of RAW 246.7 cells on biomimetic surface under simulated diabetic environment Real-time quantitative polymerase reaction (RT-qPCR) was used to detect the effect of bionic surface on the expression of M1 phenotype marker genes (CD86, IL-1) and M2 phenotype marker genes (CD0206, IL-10) of macrophages under simulated diabetic environment. o Take out from C, 37 o C water bath, centrifuge and discard the supernatant, add freshly prepared DMEM high-glucose medium containing 10% fetal bovine serum, repeatedly blow to form a cell suspension, and then transfer it into a culture bottle and place it at 37 o C. Culture in a constant temperature incubator with saturated humidity and 5% CO2, and change the medium every other day. After 3-4 days of subculture, take the vigorously growing RAW 246.7 cells, digest them with 2.5 g / L trypsin, and prepare them with DMEM culture medium containing 10% fetal bovine serum to a cell density of 2×10 4 / mL of cell suspension was inoculated on the surface of different samples and cultured for 1 d and 3 d to evaluate the effects of different materials on the phenotype of macrophages. The culture medium was discarded and gently washed with PBS. Total RNA was extracted using Trizol solution. The RNA concentration was measured using Nanodrop 1000 micro-volume UV spectrophotometer and adjusted to 150 ng / μL. Then, a reverse transcription system (TaKaRa PrimeScript TM RT reagent kit) RNA was reverse transcribed to synthesize cDNA. Then TaKaRa SYBR Premix Ex TaqTM II was used for real-time quantitative polymerase chain reaction (qRT-PCR). The average cycle threshold (Ct) of each target gene was normalized with the Ct value of GAPDH to obtain the relative expression of bone-related genes. The results are shown in Figure 1 In the DM environment, macrophages have an M1 pro-inflammatory phenotype, and TiCu and LMD-A-5h promote the secretion of inflammatory factors and promote the M1 phenotype. The LMD-A surface inhibits the M1 phenotype and promotes the M2 healing phenotype.

[0023] 3. Detection of polarization state of MC3T3-E1 cells in a remodeling and healing environment simulating diabetic environment The above RAW 246.7 cells were cultured at 2×10 4 / mL cell suspension was inoculated on the surface of different samples and cultured for 3 days. After reaching the time point, the culture medium was collected and MC3T3-E1 cells were cultured for another 7 days. Subsequently, total RNA was extracted using Trizol solution, and the RNA concentration was measured using a Nanodrop 1000 micro-volume UV spectrophotometer and adjusted to 150 ng / μL. Subsequently, a reverse transcription system (TaKaRa PrimeScript TM RT reagent kit) RNA was reverse transcribed to synthesize cDNA. Then TaKaRaSYBR Premix Ex TaqTM II was used for real-time quantitative polymerase chain reaction (qRT-PCR). The expression of ALP, OPN, COLI, and Runx2 genes in MC3T3-E1 cells was calculated to evaluate the effect of the diabetic microenvironment remodeled by different alloy bionic surfaces on osteoblast differentiation. The results are shown in Figure 2 The osteogenic effect of LMD-A group was the best, that of LMD-A-5h group was the worst, and that of TiCu group was slightly better than that of Ti group, but there was no significant difference. The surface of LMD-A reshapes the bone healing environment by regulating the phenotype of macrophages.

[0024] 4. Testing of antibacterial properties of bionic surfaces in a simulated diabetic environment Staphylococcus aureus (ATCC6538), a common pathogen in orthopedic surgery, was selected as a model bacterium, and the plate quantitative method was used to analyze the effects of different sample surfaces on bacterial viability. Briefly, the samples were placed in a 48-well plate and prepared with a PBS solution containing 25.5 mM glucose at a concentration of 1×10 7 CFU / mL bacterial suspension, add 1 mL of bacterial solution to each well to immerse the sample, and culture at 37 °C with continuous shaking (60 r / min) for 24 h. Remove the bacterial solution, transfer the sample to 5 mL of fresh PBS solution, and then vortex for 1 min to collect the adhered bacteria. Finally, take 50 μL of bacterial suspension and inoculate it on a sterile agar plate. After incubation for 24 h, count the number of colony units formed. The antibacterial rate of different material surfaces was calculated according to formula 1, where N e is the number of colonies formed after different samples are cultured with bacteria, N c50 μL 1×10 7 CFU / mL refers to the number of colony units formed by bacterial culture.

[0025] (1) FE-SEM was used to observe the bacterial morphology on different rough surfaces. Specifically, 1 mL of bacterial suspension (1×10 7 CFU / mL) were incubated with samples for 24 h. After removing the culture medium, the samples were washed three times with PBS. Bacteria were fixed on different surfaces using 4% paraformaldehyde at 4 °C. Subsequently, the samples were dehydrated in gradient ethanol (50%, 60%, 70%, 80%, 90% and 100%, v / v) for 10 min. Finally, the samples were dried at room temperature and then sprayed with gold. FE-SEM was used for observation. The results are shown in Figure 3 The bacteria on the surface of TiCu and LMD-A groups were in a dead state, such as shrinkage and damage, and both had excellent bactericidal properties, with TiCu having the best bactericidal effect. The LMD-A-5h group had no bactericidal effect, but the bacteria on its surface also appeared dead.

[0026] 5. Detection of polarization state of macrophages by RNA sequencing RNA-seq transcriptome sequencing technology was used to analyze the expression of genes, metabolic pathways, and signaling pathways of macrophages on bionic surfaces in a simulated diabetic environment. The results are shown in Figure 4-9 Compared with Ti, LMD-A upregulated 1019 genes and downregulated 1109 genes. GO functional gene enrichment analysis showed that the pathway corresponding to the downregulated genes was the inflammation inhibition pathway JAK-STAT, and the pathway corresponding to the upregulated genes was the activity of NADH dehydrogenase, which was closely related to mitochondrial energy metabolism. KEGG metabolic pathway analysis showed that the downregulated pathway was an inflammation-related pathway, and the upregulated pathway was a glycosaminoglycan biosynthesis-related pathway, and glycosaminoglycan had anti-inflammatory properties.

[0027] In summary, the copper-containing titanium alloy porous bionic surface that can achieve in-situ timed release of Mg and Cu elements provided by the present invention has the most obvious effect on regulating the polarization of macrophage M2 phenotype, and has the most excellent osteogenic and anti-inflammatory functions. This invention is expected to completely solve the clinical pain point of bone healing failure of titanium-based implants, which is common in diabetic patients, from the source, and can be applied to the field of surgical implant treatment devices for diabetic patients.

[0028] Although the present invention has been disclosed as above in some embodiments, it is not intended to limit the present invention. Any technical personnel in this field can make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the main purpose and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

Claims

1. A copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions, characterized in that: The surface is a porous composite bionic surface with magnesium-rich pores, a ligament width of 0.5-10.5 μm, and a thickness of 3-20 μm.

2. A method for preparing a copper-containing titanium alloy bionic surface based on the timed release of Mg and Cu ions according to claim 1, characterized in that: The preparation method comprises the following steps: preparing a copper-titanium alloy ingot by smelting in a vacuum consumable arc furnace, then forging the copper-titanium alloy ingot blank, heat treating it, cooling it, obtaining an experimental sample by wire cutting, polishing the sample surface with sandpaper, then placing the experimental sample in a crucible, pouring Mg particles into the crucible until the Mg particles completely cover the sample surface, and performing dealloying treatment in a muffle furnace under an argon environment to obtain a bionic surface.

3. The method for preparing a copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions according to claim 2, characterized in that: The copper-containing titanium alloy has a Cu content of 0-10 wt.%.

4. The method for preparing a copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions according to claim 2, characterized in that: The forging temperature is 900-1200°C.

5. The method for preparing a copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions according to claim 2, characterized in that: The heat treatment temperature is 700-900° C., and the heat treatment time is 0-2 h.

6. The method for preparing a copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions according to claim 2, characterized in that: The experimental sample obtained by the wire cutting is a disc with a diameter of 10 mm and a thickness of 2 mm.

7. The method for preparing a copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions according to claim 2, characterized in that: The sandpaper is at least one of 60#, 120#, 180#, 240#, and 1000# to adjust the surface roughness of the alloy.

8. The method for preparing a copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions according to claim 2, characterized in that: The Mg particles are high-purity magnesium particles.

9. The method for preparing a copper-containing titanium alloy bionic surface based on the time-sequential release of Mg and Cu ions according to claim 2, characterized in that: The dealloying treatment temperature is 700-900° C., and the holding time is 0-3 h.